Successful outcome of therapy of acute hepatitis C following sexual and parenteral exposure – report of two cases - Mazur, Katarzyna; Mania, Anna; Kemnitz, Pawel; Figlerowicz, Magdalena; Służewski, Wojciech (Clinical and Experimental Hepatology, 2016)
Acute hepatitis C (AHC) remains difficult to diagnose due to its asymptomatic course. The manuscript presents two children with AHC after known sexual and parenteral exposure, which allowed for close monitoring. Both developed increased aminotransferase activity, though the viral load was significantly higher after parenteral exposure. Lack of hepatitis C virus (HCV) clearance led to therapy with recombinant interferon- with good toleration and response. The conclusion is that treatment of AHC was effective and well tolerated.